PENGARUH PENGGUNAAN STRATEGI MIND MAPPING TERHADAP KEMAMPUAN MENULIS SISWA KELAS V SD PADA TEMA LINGKUNGAN SAHABAT KITA DI SD NEGERI 101931 PERBAUNGAN - Ayu Elvira; Dalimawaty Kadir (Bajang Institute, 2025)
Mind Mapping Strategy is a mind mapping activity using creative, effective note-taking that will map our thoughts very simply. The use of mind mapping in learning at school can create an interesting learning atmosphere for students, motivate students and make it fun when students study the material. Apart from that, mind mapping presents the relationship between concepts of a subject matter which are represented in a network of concepts starting from the core of the problem to the supporting parts that have a relationship with each other, so that mind mapping can form knowledge and make it easier to understand a lesson topic. This research aims to analyze the effect of using mind mapping strategies on the writing abilities of fifth grade elementary school students on the environmental theme of our friends at SD Negeri 101931 Perbaungan. The research uses quantitative research. This research uses research instruments in the form of a pretest and posttest to test the effect of using mind mapping strategies on the writing ability of fifth grade elementary school students on the environmental theme of our friends at SD Negeri 101931 Perbaungan. Based on research on the influence of the mind mapping method on the writing ability of Grade V students of SD Negeri 101931 Perbaungan. So it can be concluded that there is an influence of the mind mapping method on the writing ability of Class V students at SD Negeri 101931 Perbaungan. This is known based on the t hypothesis test, the final data shows that tcount is greater than ttable or 2,782 > 1,717 with a significance level of α= 0.05, so it can be concluded that the mind mapping method has a positive and significant influence on the writing ability of Class V students at SD Negeri 101931 Perbaungan